Short-term effects of cadmium on leaf growth and nutrient transport in rice plants. (December 2021) - Huybrechts, Michiel; Hendrix, Sophie; Kyndt, Tina; Demeestere, Kristof; Vandamme, Dries; Cuypers, Ann
Highlights: Cadmium evokes quickly a reduction of biomass and leaf growth in O. sativa . The glutathione metabolism is vital to oppose oxidative stress in O. sativa leaves. Manganese homeostasis is disturbed early in O. sativa after cadmium exposure. Cadmium increases abscisic acid in the leaf growth zone of O. sativa plants. Abstract: Consumption of rice grains contaminated with high concentrations of cadmium (Cd) can cause serious long-term health problems. Moreover, even low Cd concentrations present in the soil can result in the abatement of plant performance, leading to lower grain yield. Studies examining the molecular basis of plant defense against Cd-induced oxidative stress could pave the way in creating superior rice varieties that display an optimal antioxidative defense system to cope with Cd toxicity. In this study, we showed that after one day of Cd exposure, hydroponically grown rice plants exhibited adverse shoot biomass and leaf growth effects. Cadmium accumulates especially in the roots and the leaf meristematic region, leading to a disturbance of manganese homeostasis in both the roots and leaves. The leaf growth zone showed an increased amount of lipid peroxidation indicating that Cd exposure disturbed the oxidative balance. We propose that an increased expression of genes related to the glutathione metabolism such as glutathione synthetase 2, glutathione reductase and phytochelatin synthase 2, rather than genes encoding for antioxidant enzymes, is important in combating early Cd toxicity within the leaves of rice plants. Furthermore, the upregulation of two RESPIRATORY BURST OXIDASE HOMOLOG genes together with a Cd concentration-dependent increase of abscisic acid might cause stomatal closure or cell wall modification, potentially leading to the observed leaf growth reduction. Whereas abscisic acid was also elevated at long term exposure, a decrease of the growth hormone auxin might further contribute to growth inhibition and concomitantly, an increase in salicylic acid might stimulate the activity of antioxidative enzymes after a longer period of Cd exposure. In conclusion, a clear interplay between phytohormones and the oxidative challenge affect plant growth and acclimation during exposure to Cd stress.